2011
DOI: 10.1055/s-0039-1699520
|View full text |Cite
|
Sign up to set email alerts
|

Collagen sheet dressings for cutaneous lesions of toxic epidermal necrolysis

Abstract: Toxic epidermal necrolysis (TEN) is associated with a significant mortality of 30–50% and long-term sequelae. Treatment includes early admission to a burn unit, where management with precise fluid, electrolyte, protein, and energy supplementation, moderate mechanical ventilation, and expert wound care can be provided. Specific treatment with immunosuppressive drugs or immunoglobulins did not show an improved outcome in most studies and remains controversial. We have treated the cutaneous lesions of seven patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…7 A Study by S Bhattacharya et al showed excellent results by using Collagen sheets on patients with toxic epidermal necrolysis (TEN). 8 Mason and read demonstrated that microfibrillar collagen triggered adhesiveness of platelets and stimulated the release phenomenon producing aggregation of nearby platelets. 9 Piatkowski et al established that pressure ulcers treated with collagen dressings showed a superior response of healing by having a positive effect on angiogenesis and superior reduction of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…7 A Study by S Bhattacharya et al showed excellent results by using Collagen sheets on patients with toxic epidermal necrolysis (TEN). 8 Mason and read demonstrated that microfibrillar collagen triggered adhesiveness of platelets and stimulated the release phenomenon producing aggregation of nearby platelets. 9 Piatkowski et al established that pressure ulcers treated with collagen dressings showed a superior response of healing by having a positive effect on angiogenesis and superior reduction of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is essential factor in regeneration, it plays a crucial role in cell adhesion , migration and wound healing. [11][12][13][14] Collagen dressing has moderate to high absorption capacity, non adhesive and non hydrating in characteristics. This dressing is beneficial in various ways.…”
Section: Introductionmentioning
confidence: 99%